Kavitrayakavitā vimarśanamu - Vēṅkaṭasubbarāmayya, Guṟṟamu (SAMP early 20th-century Indian books project, 1933)
Study of Telugu poets, Nannaya, 11th cent., Tikkana, 1220-1300, and Yerrapragada, 14th cent.